Response of CARI Devendra dual-purpose chicks to supplemental zinc levels - DEO, CHANDRA; SHRIVASTAVA, H P; MANDAL, A B; TYAGI, PRAVEEN K (The Indian Journal of Animal Sciences, 2011)
An experiment was conducted in CARI Devendra dual-purpose chicks to find out the optimum level of supplemental zinc. Significantly lower body weight gain was observed in chicks fed with basal diet (29 mg zinc/kg) than those fed diets with 40, 50, 60 and 70 mg Zn/kg during 6-9 and 0-9 weeks of growth phases. However, body weight gain during 0-6 weeks and feed intake during different growth phases did not differ significantly due to different dietary zinc levels. Feed conversion efficiency was also significantly poor in chicks fed the lowest dietary Zn level in comparison to other dietary treatments during 6-9 and 0-9 weeks of age. During 0-6 of age, feed efficiency did not change due to dietary treatments. Hock circumference was significantly lower at low dietary Zn level (29 mg/kg) than other dietary treatments. Pre-slaughter live weight and evicerated weight were significantly lower at low level of Zn than the other dietary treatments. Shrinkage loss was significantly higher at low Zn level. The liver weight was significantly lower at highest level of Zn. The dressed weight, and giblet, heart and gizzard weights did not change due to dietary treatments. Based on the results it was concluded that a dietary level of 40 mg zinc per kg diet was found optimum for growth performance and carcass yield in CARI Devendra dual-purpose chicks.